2011
DOI: 10.5367/te.2011.0036
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study of the Influences of Recreational Park Visitation: The Case of US National Park Service Sites

Abstract: The authors examine which variables influence recreational visitation at 353 US National Park Service (NPS) sites. The paper provides evidence that variables other than lagged visitation, including various site designators, various regional dummies, lagged RDPI (inferior), alternative sites (complementary effect), the regional 9/11 terrorist attacks variable and the regional terrorism threat level variable (increase in threat level decreases visitation) are statistically and economically significant. Generally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…The existing literature on economic valuation of UNESCO World Heritage parks (Alexandrakis et al, 2019) such as GNP is relatively scarce. Certainly, there are no comprehensive studies on the economic values of attributes found in the Galapagos Islands (Peñaherrera et al, 2012), and there is a lack of information on tourist preferences in UNESCO parks and policy guidelines or suggestions to better allocate their resources (McIntosh and Wilmot, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The existing literature on economic valuation of UNESCO World Heritage parks (Alexandrakis et al, 2019) such as GNP is relatively scarce. Certainly, there are no comprehensive studies on the economic values of attributes found in the Galapagos Islands (Peñaherrera et al, 2012), and there is a lack of information on tourist preferences in UNESCO parks and policy guidelines or suggestions to better allocate their resources (McIntosh and Wilmot, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, given the demonstrated significance of the terrorist attack against the US (McIntosh & Wilmot, 2011), several dummy variables were constructed to capture the potential impact/"structural change" from this event. The first dummy variable (TDY) takes the value 1 after 2001 terrorist attack (TDY = 1 in 2002-2006, 0 otherwise), while TDUM equals 1 at the time of the terrorist attack (TDUM = 1 in 2001, 0 otherwise).…”
Section: Wilmot and Mcintoshmentioning
confidence: 99%
“…The basis for the inclusion of economic variables derives from the work of McIntosh and Wilmot (2011). Many of the macroeconomic variables were obtained from the Federal Reserve Economic Database (Federal Reserve Bank of St. Louis, 2010), including real disposable personal income (RDPI) (series: DPIC 96), exchange rates (ERATE) (series: TWEXBANL), and population (POP) (series: POPTHM).…”
mentioning
confidence: 99%
“…These equations offer justification for the estimation of regression equations outlined in the empirical model (to be discussed in the next section). To explain the above-derived quantity of recreational goods (that is, the park visit), we started with the typical demand model of national park visitation, commonly used in tourism economics literature (Johnson andSuits, 1983, McIntosh andWilmot, 2011). This model, explains the number of park visits as a function of both the destination characteristics (accessibility, season, air quality, etc) and the characteristics of the social and economic characteristics of potential visitors (transportation cost, consumer confidence, relative price of other goods, etc).…”
Section: Max U(x)mentioning
confidence: 99%
“…Following Johnson and Suits (1983) and McIntosh and Wilmot (2011), we measured the dependent variable as the total monthly recreational visits to a national park. One limitation in such quantitative models of tourism flow and park visitation demand is the identification of appropriate independent variables (Chen et al, 2008).…”
Section: Max U(x)mentioning
confidence: 99%